2019
DOI: 10.1530/obabs.01.rfc1.6
|View full text |Cite
|
Sign up to set email alerts
|

Plate size and food consumption: A pre-registered experimental study in a general population sample

Abstract: Background: There is considerable uncertainty regarding the impact of tableware size on food consumption. Most existing studies have used small and unrepresentative samples and have not followed recommended procedures for randomised controlled trials, leading to increased risk of bias. In the first pre-registered study to date, we examined the impact on consumption of using larger versus smaller plates for self-served food. We also assessed impact on the underlying meal micro-structure, such as number of servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…To detect a small effect (d = 0.2) with power = 0.90, alpha = 0.05 and a conservative estimate of 0.5 for within person correlations [ 25 ], 265 participants were needed. Based on the previous plate size study [ 11 ], in which randomisation occurred immediately prior to a single study session, a dropout rate of no more than 5% was anticipated (see pre-registered protocol for more details: https://osf.io/dj3c6/ ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To detect a small effect (d = 0.2) with power = 0.90, alpha = 0.05 and a conservative estimate of 0.5 for within person correlations [ 25 ], 265 participants were needed. Based on the previous plate size study [ 11 ], in which randomisation occurred immediately prior to a single study session, a dropout rate of no more than 5% was anticipated (see pre-registered protocol for more details: https://osf.io/dj3c6/ ).…”
Section: Methodsmentioning
confidence: 99%
“…We are only aware of one pre-registered study that has applied rigorous randomised controlled trial procedures to examine the effects of tableware on selection and consumption [ 11 ]. This study found no clear evidence of a statistically significant difference in either the total amount selected or consumed over a whole meal period when food was self-served on to a smaller (23 cm diameter) compared to a larger (29 cm diameter) round plate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although outside the remit of this chapter, it is worth noting that both the interpretation and application of System 1 and System 2 thinking in designing nudges and the effectiveness of nudges has been questioned (see for example Gigerenzer 2015; Kuehnhanss 2018). The evidence for nudges using plate sizes described in the introduction, for example, is weak (Kosīte et al 2019). Thus, a focus on using nudges as a way to change behavior may take public servants attention away from other, more effective approaches.…”
Section: The Problem With Focusing On Nudgementioning
confidence: 99%